A Qualitative Analysis of Experiences With Food-Related Activities Among People Living With Parkinson Disease and Their Care-Partners. (January 2023) - Ferguson, Christine C.; Jung, Seung Eun; Lawrence, Jeannine C.; Douglas, Joy W.; Halli-Tierney, Anne; Bui, Chuong; Ellis, Amy C.
Objectives: The purpose of this qualitative study was to explore factors associated with the ability of people with PD to perform food-related activities (FRAs).Methods: Eleven dyads, older adults with Parkinson disease (PD) and their care-partners ( n = 22), completed virtual semi-structured interviews guided by the Social Cognitive Theory (SCT) that were independently analyzed by two coders via directed content analysis.Results: The following themes were identified—(1) Personal: perception of a healthy diet, perception of how nutrition influences PD, confidence in following a healthy diet, and barriers to performing FRA; (2) Environmental: previous sources of nutrition information and willingness to changing their diet with a registered dietitian; and (3) Behavioral: modifications to FRA due to food-medication interactions, and skills necessary to maintain a healthy diet.Discussion: Findings from this study highlight the need for nutrition intervention research to inform evidence-based guidelines in order to provide tailored education for people with PD and care-partners.